Microbial contamination in dental unit waterlines - Souza-Gugelmin,Maria Cristina Monteiro de (2003)
The quality of water in a dental unit is of considerable importance because patients and dental staff are regularly exposed to water and aerosol generated from the dental unit. The aim of this study was to evaluate the occurrence of microbial contamination in dental unit waterlines. Water samples were collected aseptically from the waterlines (reservoir, triple-syringe, high-speed) of 15 dental units. After serial dilution to 1:10(6) in APHA, the samples were seeded by the pour-plate technique and cultured in plate count agar (Difco) for 48 h at 32ºC. Analysis was based on the number of colony forming units (CFU). The Wilcoxon non-parametric test indicated that the levels of water contamination were highest in the triple-syringe (13 of 15) and in the high-speed (11 of 15); both levels were higher than those of the water reservoir. There was no significant statistical difference between the level of contamination in the triple-syringe and the high-speed as determined by the Mann-Whitney test [p(H0) = 40.98%; Z = - 0.2281]. Because biofilm forms on solid surfaces constantly bathed by liquid where microorganisms are present, these results indicate that the water in the dental unit may be contaminated by biofilm that forms in these tubules.